Spinal Cord Subacute Combined Degeneration Mimicked by Copper Deficiency: A Case Report - Zekarias Seifu Ayalew; Mehariw Wondimu Netsere; Matyas Adugna Abebe; Surafel Tilahun Maru; Gebeyehu Tessema Azibte; Aynalem Demsis Biza; Getnet Yigzaw Mossie (Clinical Case Reports)
ABSTRACT This case report underscores the diagnostic challenge of copper‐deficiency myelopathy (CDM) and subacute combined degeneration (SCD) due to their similar clinical presentations. A 32‐year‐old male farmer initially treated for SCD with normal vitamin B12 levels showed no improvement, leading to a delayed diagnosis of CDM. His symptoms included sensory ataxia, spasticity, and sensory loss in the lower extremities, which resolved with oral copper supplementation. Clinicians should maintain a high index of suspicion for CDM, especially in patients who are unresponsive to B12 therapy. This case also highlights that marginal copper deficiency can cause significant neurological symptoms and that early intervention with copper supplementation can lead to full recovery, preventing irreversible damage. It also emphasizes the need for comprehensive testing, including copper levels, in cases of atypical myelopathy to avoid a delayed diagnosis.